ISLAM AND ECOTHEOLOGY (A Study of the Message of the Qur'an to Preserve Environmental Wisdom) - Ali Mursyid Azisi; Andi Rafida; Muhammad Jamaluddin; Denu Rahmad; Siti Miftakuz Zaqiyah (al-Afkar, Journal For Islamic Studies, 2023)
A single This research article examines the role of religious values ​​in preventing environmental damage on earth. Religion and the environment are inseparable. Such an understanding is not correct. So far, religion is considered not to have an important role in protecting the environment and making people aware of protecting nature. Whereas in Islam, it has been stated in the Qur'an and Hadith that humans must care about the environment. The purpose of human life is not only to worship God but also to maintain the relationship between humans and nature. As has been applied in Islam which teaches about Rahmatan Lil 'Alamin, from there humans are ordered to not only have mercy or do good to humans, but also to nature, be it plants, rocks, the environment, and so on. The research method used in this article uses a qualitative approach with literature study, which collects data in the form of journals, books, and supporting references that are relevant and accountable. It is very important to protect the environment from inefficient plastic processing for the sake of a clean and healthy life. In Islam, it is also required to live a healthy life. The results of this study are about the importance of humans in protecting the environment and the role of religion in Him, as well as the efforts of religious communities in dealing with plastic pollution to preserve the environment.